Monitoring the structural health of a reinforced concrete shear wall residential building in Lima, Peru, using a raspberry shake 4d sensor - Sifuentes Jiménez, Armando Israel (2022)
Lima, the capital of Peru, has not suffered from a great earthquake since 1746, making this a prone Mw 8.8 earthquake area according to seismological studies. In this context, seismic structural health monitoring presents an opportunity to assess rapidly buildings after a great earthquake and protect inhabitant from those buildings with high risk of collapse due to aftershocks. A basic seismic structural health monitoring arrangement of a fifteenth-floor residential building is presented using a low-cost sensor called Raspberry Shake 4D. The implemented sensor incorporates both a vertical velocity geophone and three orthogonally positioned microelectromechanical systems accelerometers. The building is a reinforced concrete shear walls structure located in Comas, north of Lima. More than thirty seismic events have been recorded, including the Mw 8.0 Lagunas earthquake (05/26/2019) and the Mw 5.8 (22/06/2021) with epicentral distances of 709 km and 94 km, respectively. Acceleration as high as 150 cm/s2 and as low as 2 cm/s2 have been recorded. It was possible to obtain fundamental frequencies of vibration in longitudinal and transversal directions of the building from the response calculated using the wavelet transform that have a good agreement with results of microtremor measurements performed at different floors. The computed scalograms for seismic records showed important values of energy amplitudes for the fundamental frequencies of the building. Finally, theoretical fundamental frequencies were obtained from a 3D finite element model and an elastic analysis.